How to manage balloon entrapment during percutaneous coronary intervention of a calcified lesion “Case report” - Zaoui, Nassime; Boukabous, Amina; Bachir, Nadhir; Irid, Nabil; Terki, Ali (Journal of Cardiology and Cardiovascular Medicine, 2022)
Percutaneous coronary angioplasty is a minimally invasive procedure aimed at unclogging a coronary artery with a low complication rate (with a serious complication rate of 3% to 7% and a mortality rate of 1.2%). Device entrapment during PCI is a rare but life-threatening complication that occurs in < 1% of PCIs and balloon entrapment comes second after coronary guidewires. We present the case of 68-years-old man, smoker, hypertensive and type2 diabetic that presents angina with evidence of ischemia on myocardial tomoscintigraphy and in whom the radial coronary angiography reveals a tight calcified mid LAD stenosis. During his PCI and after dilatation with an NC balloon 2.5 × 12 the latter refuses to deflate and remains trapped in the lesion with the appearance of pain and ST-elevation despite several attempts to dilute the product in the inflator and to burst it by overexpansion. Traction on the balloon resulted in the deep intubation of the guiding-catheter, which comes in contact with the trapped balloon, and the rupture of the latter’s hypotube, which remains inflated at the site of the lesion and mounted on the 0.014 guidewire. We put a second 0.014 guidewire distally in the LAD and twisted with the distal part of the first guidewire, then we introduced a second balloon 2.0 × 20 over the second guidewire until the distal part of the guiding-catheter and inflated to trap the stucked balloon. We gradually removed this emergency assembly that allowed us to retrieve the trapped balloon. The control injection revealed a thrombotic occlusion of the LAD treated by thrombectomy and anti-GPIIbIIIa followed by a DES 2.75 × 28 placement. The patient was discharged 48 hours later with a good LVEF. The possible balloon entrapment mechanisms are an acute recoil of a highly calcified lesion with compression of the incompletely deflated balloon, which seems to be the case in our patient, strangulation of the proximal balloon end by the guiding-catheter if the balloon is removed before complete deflation and break or bend of the hypotube. The solutions in case of undeflatable balloon entrapment are to dilute the product in the inflator, to burst it by overexpansion, to pierce it through a stiff guidewire (or through its other end on a Microcatheter or OTW balloon), to cut its outer part and let it empty passively, to introduce a second guide-wire and perform a Buddy-Balloon or to transfer the patient to Surgery. Material entrapment remains a rare but life-threatening complication, its eviction requires the choice of material size and gentle manipulations (small balloons in the event of a calcified lesion) and its management uses different techniques, the choice of which depends on the clinical and anatomical situation.